Karakteristik Petrologi Batuan Daerah Banturung Kecamatan Bukit Batu Kota Palangka Raya - I Putu Putrawiyanta; Novalisae Novalisae; Noveriady Noveriady; Neny Fidayanti; Irga Loti Rante; Hendrik Brianto (Universitas Islam Raden Rahmat, Malang, 2024)
The Banturung area, a sub-district in Bukit Batu District, Palangka Raya City, mostly consists of rocky hill morphology. This research aims to determine the characteristics of rocks in the Banturung area based on petrological analysis and direct observation of rock outcrops at the research location. Characteristics can be determined by direct field observation or by macroscopic observation, where what is observed are physical properties including color, structure, texture, mineral composition and also the formation process. From the results of the analysis it is known that the characteristics of the rocks at the research location include igneous rock types and there are several mineral compositions with an average percentage of quartz 52.5%, plagioclase 21.3%, mica 8.6%, biotite 5%, hornblende 11, 3% and 1.3% pyrite mineral.